PENGARUH FITUR DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI NETFLIX (Studi Kampus Pada Mahasiswa Universitas Nasional Karangturi Semarang) - Imannata, Yehuda; Herdian Dito, Anoki; Risma Rukma Adi, Pradipta (J-LEE - Journal of Law, English, and Economics, 2023)
The research "The Influence of Features and Prices on the Purchase Decision of the Netflix Application" (Case Study on Students of the Karangturi National University, Semarang) aims to determine the effect of features and prices on the purchase decision of the Netflix video streaming service at Karangturi National University. The variables of this study have three variables, namely the independent variable (X1) with features, the independent variable (X2) namely price, and the dependent variable (Y) namely purchase decision. This study used a purposive sampling technique. The data analysis used is descriptive analysis of research data, respondent demographics, and research data statistics. The data that has been processed using the SPSS 22.0 program produces a hypothesis test as follows:Based on the test conducted by the results of the t test, it can be seen that features and price do not significantly and positively influence purchasing decisions for students at Karangturi National University, Semarang. From the results of the f test it can be concluded that variable X (price and features) has a simultaneous influence on variable Y (purchasing decision). Keywords: Video Entertainment On Demand (VOD), Netflix, Decision Making.